Learning Boost C++ libraries : solve practical programming problems using powerful, portable, and expressive libraries from Boost - Mukherjee, Arindam (Community experience distilled., 2015)
If you are a C++ programmer who has never used Boost libraries before, this book will get you up-to-speed with using them. Whether you are developing new C++ software or maintaining existing code written using Boost libraries, this hands-on introduction will help you decide on the right library and techniques to solve your practical programming problems.